2023
DOI: 10.3390/ani13081409
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Resistance Genes in Broiler Chickens in Tunisia

Abstract: Colistin is a polymyxin antibiotic that has been used in veterinary medicine for decades, as a treatment for enterobacterial digestive infections as well as a prophylactic treatment and growth promoter in livestock animals, leading to the emergence and spread of colistin-resistant Gram-negative bacteria and to a great public health concern, considering that colistin is one of the last-resort antibiotics against multidrug-resistant deadly infections in clinical practice. Previous studies performed on livestock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…A total of 81 (41.5%) of the 195 animals tested positive for mcr-1 with positive cases on all farms. These findings corroborate the emergence of colistin resistance in farm animals in Tunisia and suggest that investigating antibioticresistance genes (ARGs) might contribute to epidemiological research on antimicrobial resistance dissemination [10].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…A total of 81 (41.5%) of the 195 animals tested positive for mcr-1 with positive cases on all farms. These findings corroborate the emergence of colistin resistance in farm animals in Tunisia and suggest that investigating antibioticresistance genes (ARGs) might contribute to epidemiological research on antimicrobial resistance dissemination [10].…”
Section: Introductionsupporting
confidence: 70%
“…Previous studies utilizing culture-dependent techniques on farm animals in Tunisia revealed the prevalence of colistin-resistant Gram-negative bacteria. In a recent investigational study, DNA analysis for ten known mcr genes was conducted on cloacal swabs from 195 broiler chickens from six farms in Tunisia [ 10 ]. A total of 81 (41.5%) of the 195 animals tested positive for mcr-1 with positive cases on all farms.…”
Section: Introductionmentioning
confidence: 99%
“…With limited antibiotic options for infections caused by CR pathogens, polymyxins are the mainstay therapy. However, reports on colistin-resistant clinical isolates are increasing globally, suggesting diminishing treatment options for CR-GNB infections and a high risk of difficult-to-treat (DTT) pathogens [ 20 , 49 ]. We observed colistin resistance, ranging from 60 to 100%, among A. baumannii and P. aeruginosa isolates.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 116 (55.8%) strains carrying mcr-1 on IncHI2, IncI, IncP, and IncFI plasmids were detected among 208 E. coli isolates [72][73][74][75]192,193,282]. ISApl1 and pap2 were upstream and downstream of mcr-1, respectively [192], and class one integrons were associated with virulence genes, including markers of EHEC (stx1 and stx2) and UPEC (papC), and 19 other antimicrobial determinants, including ESBL and pAmpC genes, conferring resistance to five antimicrobial classes in some mcr-positive isolates [74,282] (Table 2). The mcr-positive isolates were extensively diversified, belonging to 17 STs, including HiR-ExPEC clones ST10, ST117, and ST69 (Table 2).…”
Section: Northern Africa Tunisiamentioning
confidence: 99%